2009
DOI: 10.1016/j.anclin.2009.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Surgery in the Patient with Renal Dysfunction

Abstract: Preoperative evaluation of patients with renal dysfunction often requires the collaborative efforts of the primary care physician, nephrologist, surgeon, and anesthesiologist. Renal dysfunction is typically a spectrum of disease with multisystem effects. Optimization of preexisting medical issues is the key, as is a thorough understanding of the potential perioperative risks for further renal injury. Surgical or anesthetic techniques may require alteration for the patient with significant renal dysfunction. Id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…1 A graph shows the odds ratios with 95% CIs for the key risk factors in the multivariable analysis. Numerous reports [2,14,19,23,33] have assessed various factors contributing to postoperative KD and described the consequences of KD on surgical and anesthetic management [1,5,13,16,19]. Reported risk factors are dehydration, increased age, diabetes, shock, heart failure, nephrotoxic medications (NSAIDs, aminoglycosides, angiotensin-converting enzyme inhibitors, diuretics, angiotensin II receptor antagonists, opiates), iodinated contrast agents, and preexisting KD [5].…”
Section: Discussionmentioning
confidence: 99%
“…1 A graph shows the odds ratios with 95% CIs for the key risk factors in the multivariable analysis. Numerous reports [2,14,19,23,33] have assessed various factors contributing to postoperative KD and described the consequences of KD on surgical and anesthetic management [1,5,13,16,19]. Reported risk factors are dehydration, increased age, diabetes, shock, heart failure, nephrotoxic medications (NSAIDs, aminoglycosides, angiotensin-converting enzyme inhibitors, diuretics, angiotensin II receptor antagonists, opiates), iodinated contrast agents, and preexisting KD [5].…”
Section: Discussionmentioning
confidence: 99%
“…16 The majority of articles reported that maintenance dialysis was at a higher risk of postoperative complications after major surgery, including surgery on the heart, lung, spine, and abdominal aortic aneurysm, and laparoscopic cholecystectomy, [17][18][19][20][21][22] whereas there have been controversial results in carotid endarterectomy. [23][24][25][26][27] Moreover, postoperative morbidity and mortality rates were much higher in emergency abdominal surgery than elective operations in patients on hemodialysis.…”
Section: Discussionmentioning
confidence: 99%
“…29 However, these percentages for control patients without end-stage renal disease were not presented in the article similarly to most other reports. [16][17][18][19]21,22,28 As far as we know, the current study is the first cohort review comparing the frequency of complications and oncological outcomes after surgical resection for CRC between distinct CKD stages. Longer life expectancy has been expected in recent decades, which in turn results in a higher frequency than ever of a wide range of morbidity including CRC and CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to more frequent bleeding, infection complications, and side effects of anesthesia, surgery in chronic renal failure patients is significantly more risky than in normal renal function individuals. 14, 15 Savage et al 16 reported that medical treatment with antibiotics is a viable alternative to surgery for patients without systemic sepsis or neurological symptoms. However, the limited literature does not clarify the role and outcome of medical treatment or surgical intervention, 17 particularly in patients with ESRD, and thus close clinical follow-up is required.…”
Section: Discussionmentioning
confidence: 99%